Role of PVA Flakes in Promoting Self-Degradation of Sodium Metasilicate-Activated Cement under a Hydrothermal Environment at 150°C - Sugama, T.; Pyatina, T.; Muraca, A. (Journal of Technology Innovations in Renewable Energy, 2013)
We investigated the effect of flakes of polyvinyl alcohol (PVA) on the self-degradation of sodium metasilicate (SMS)-activated slag/Class C fly ash cement, which is used as temporary sealer for fractures in Enhanced Geothermal System (EGS) wells under a hydrothermal environment at ³150°C and at pressure of 1000 psi. The reactions between PVA and SMS dissolved in an aqueous medium at 85°C led to the formation of a colloidal hydroxylated silicate-cross-linked PVA gel in the cement body. This gel-incorporated cement had a compressive strength >2000 psi, so ensuring that it adequately plugs the fractures. Increasing the hydrothermal temperature to ³150°C triggered the transformation of the gel into a sol. This in-situ gel®sol phase transition played a pivotal role in promoting the cement’s self-degradation because of the extensive spreading of sol in the cement body, and its leaching from the cement. In contrast, when gel was dry heated at ³150°C, the gel®xerogel phase transformation engendered the molecular fragmentation of PVA. This fragmentation yielded polysilicate cross-linked PVA derived from the combination of extended-chain scission, carboxylation and condensation, so that it no longer served as a self-degrading promoter of cement.